PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, DAN EARNING PER-SHARE TERHADAP HARGA SAHAM - Arry Widodo; Renda Puspita Dewi (Business Management Journal, 2017)
This study also aimed to determine the effect of Current Ratio (CR), Debt to Equity Ratio (DER), and Earning per Share (EPS) to the Price Stock either partially or simultaneously. Secondary data collected based on time series and cross section from the 2008-2012 from 26 companies Costumer Goods sector. By using panel data regression analysis techniques and the Chow test and Hausman test shows that the model used in the estimation of the data is the Random Effect Model. The results showed that the independent variables, EPS significant effect on stock prices. While CR and partially DER no significant effect on stock prices. Simultaneously, CR, DER, and EPS significant effect on stock prices. Keywords: Current Ratio, Debt to Equity Ratio, Earnings per Share, Price Stock